2007
DOI: 10.1124/mol.106.030122
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Analogs, a Novel Group of “Mitocans,” as Anticancer Agents: The Importance of Being Redox-Silent

Abstract: The search for a selective and efficient anticancer agent for treating all neoplastic disease has yet to deliver a universally suitable compound(s). The majority of established anticancer drugs either are nonselective or lose their efficacy because of the constant mutational changes of malignant cells. Until recently, a largely neglected target for potential anticancer agents was the mitochondrion, showing a considerable promise for future clinical applications. Vitamin E (VE) analogs, epitomized by ␣-tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
128
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 152 publications
(156 reference statements)
3
128
2
Order By: Relevance
“…Studies with mitocans have shown exciting potential for cancer therapy since these drugs have limited side effects, and some of these compounds possess specificity for cancer cells (Neuzil et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with mitocans have shown exciting potential for cancer therapy since these drugs have limited side effects, and some of these compounds possess specificity for cancer cells (Neuzil et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic drugs acting by selectively affecting mitochondria in cancer cells, 'mitocans' (Neuzil et al, 2006(Neuzil et al, , 2007Ralph et al, 2007), are attractive for the treatment of cancer (Ko et al, 2004;Bonnet et al, 2007;Dong et al, 2007;Neuzil et al, 2007). Prime examples of such drugs are a-tocopheryl succinate (a-TOS) (Neuzil et al, 2001a, b), 3-bromopyruvate (3BP) (Geschwind et al, 2002;Ko et al, 2004) and dichloroacetate (DCA) (Bonnet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Both a-TOS and ATO have been described as anticancer drugs that target mitochondria (known as mitocans), which are thought to exert their cytotoxic effects primarily by interfering with the generation of reactive oxygen species (ROS). 8 Indeed, the exquisite sensitivity of APL to ATO treatment has been recently demonstrated to be mediated by PML-RARa oxidation and subsequent degradation in an ROS-dependent process. 9 Interestingly, Weber et al 10 demonstrated that p0 cells that lack mitochondrial respiratory chain (MRC) activity are insensitive to a-TOS toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…a-TOS, a compound epitomising the 'mitocan' group of anticancer agents (Neuzil et al, 2007a), was found to induce cell death by generation of superoxide anion radicals by targeting complex II of the mitochondria respiratory chain (Dong et al, 2008(Dong et al, , 2009. ROS, in turn, promote apoptosis by catalysing the formation of disulfite bridges between monomeric Bax, resulting in the formation of mitochondrial outer membrane channel.…”
Section: Discussionmentioning
confidence: 99%
“…One of the emerging targets for anti-cancer drugs is mitochondria that is central to induction of programmed cell death (Gogvadze et al, 2008;Trachootham et al, 2009). Our previous work has identified mitochondria as transmitters of apoptosis induced by the redox-silent analogue of vitamin E (VE) a-tocopheryl succinate (a-TOS) (Neuzil et al, , 2007a) that is selective for cancer cells (Neuzil et al, 2001a, b) and suppresses tumours in a variety of pre-clinical models (Neuzil et al, 2001b;Stapelberg et al, 2005;Wang et al, 2007;Dong et al, 2008Dong et al, , 2009). This suggests that the VE analogue is a promising anti-cancer drug that may suppress tumours by causing cell death of malignant cells as well as synergizing with other anti-cancer agents.…”
mentioning
confidence: 99%